Balance Harvest from the Forest as a Renewable Resource Using Game Theory - Ngakan Ketut Acwin Dwijendra; R. Sivaraman; Karthikeyan Kaliyaperumal; Rosario Mireya Romero-Parra (Discrete Dynamics in Nature and Society)
Forests are among the most important renewable natural resources. While having a great range of benefits, the crucial advantage of forests is the production of oxygen and the absorption of pollutants. Thus, the current article attempts to examine forest exploitation as a source of wood to prevent forest overexploitation. Three smugglers, residents, and timber companies exploit this resource. There is a competition for the perception of this common source between these factors. In this article, these interactions are considered a game in order to obtain the most probable solution in the real competition between these factors by examining this game. This answer is the balance of the game. In order to use this answer, the behavior of the players can be predicted and used in management planning. Since the amount of withdrawals of operating companies depends on the current inventory (t), the player’s behavior is determined by the system’s current state and then Markov equilibrium was obtained for them.